A research designed to develop a rubric which assesses the performance of students' problem posing [Problem tasarlama performansinin deǧerlendirilmesinde kullanılabilecek bir rubriǧin geliştirilmesine ilişkin bir araştırma] - (:unkn) unknown (My University, 2011)
In this study, an analytic rubric was designed to assess the problems posed by students in the 2008-2009 academic year. It was developed in the university first year basic physics course. The data of the research was collected, by using students' work sheets, classroom discussions and the literature about the assessment of problem posing, to find out the and assessment criteria of the rubric. Six dimensions were determined which are fluency of a problem, scientific accuracy of the problem (Compliance with the Principles of Physics), structure of the problem, number of questions produced from the problem, complexity of the problem and the solvability of the problem. It was found that; Interrater Reliability Coefficent r = 0.86 and Intrarater Reliability Coefficient r = 0.92.
Keywords: Analitic rubric; Performance assesment; Problem posing